Energy Trading and Investing: Trading, Risk Management and Structuring Deals in the Energy Markets - A Book Review - G. P., Girish; S., Vijayalakshmi (Indian Journal of Finance, 2014)
Energy trading, in particular, is not a pure science, but a complex mix of economics, finance, markets, trading, risk management, scientific tools, and rational as well as irrational behavior of energy market participants affected hugely because of business environment, macro-economic factors, market microstructure, demand-supply forces, and political factors. In the present book review, we review the book titled Energy Trading and Investing: Trading, Risk Management and Structuring Deals in the Energy Markets authored by Davis W. Edwards and published by McGraw-Hill (Finance&Investing), which highlights the relevance, criticality, and importance of the energy trading business and offers crucial insights into organizational, capital, risk management, and quantitative modeling facets for energy trading and investing. Book: Energy Trading and Investing: Trading, Risk Management and Structuring Deals in the Energy Markets Author: Davis W. Edwards Publisher: McGraw-Hill (Finance & Investing) Publication Edition: First Edition ISBN No: 978-0071629065 Price: Rs 4615 Pages: 400 Pages Binding: Hardcover